Adaptive trajectory tracking of wheeled mobile robot based on fixed-time convergence with uncalibrated camera parameters. (April 2020) - Guo, Pengfei; Liang, Zhenying; Wang, Xi; Zheng, Mingwen
Abstract: The problem of fixed-time trajectory tracking control for a wheeled mobile robot with uncalibrated camera parameters is considered. The fixed-time adaptive trajectory tracking control laws are developed. Firstly, the dynamics mode of robot system with unknown parameters is introduced and the tracking error system is given. Secondly, the problem of trajectory tracking is transformed into the problem of fixed-time stabilization for the error system by using the state and input transformations. Then, the fixed-time controller is designed based on nonsingular recursive terminal sliding mode control method, which enables the actual system to track the reference trajectory in fixed time. Finally, the simulation examples verify the validity of the conclusions. Highlights: The fixed-time adaptive trajectory tracking control laws are developed. A third-order recursive terminal sliding mode surface is proposed. The fixed-time tracking problem of robot with unknown parameters is solved. Convergent time is only determined by controllers parameters.